2017
DOI: 10.1108/nbri-04-2016-0012
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing customer satisfaction: users perspective towards online shopping

Abstract: Purpose This study aims to identify and analyse the key determinants influencing customer satisfaction towards online shopping in India. Design/methodology/approach The literature concerning major attributes of website functionality, perceived usability, perceived usefulness and customer satisfaction in online retailing were reviewed. Data were collected from 365 respondents active in online shopping for examining the constructs. The model was empirically tested using structural equation modelling. Finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
2
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 72 publications
1
34
2
13
Order By: Relevance
“…The results of this study are consisted with the previous studies of Abdeldayem [5], Tandon [13] and Kumar [7]. According to the findings of this study researcher identified that convenience have significant influence on the customer satisfaction on online shopping in the Sri Lankan context.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The results of this study are consisted with the previous studies of Abdeldayem [5], Tandon [13] and Kumar [7]. According to the findings of this study researcher identified that convenience have significant influence on the customer satisfaction on online shopping in the Sri Lankan context.…”
Section: Discussionsupporting
confidence: 52%
“…This is might be the results of the 24 hours service, fast delivery, availability of detailed information and similarity for the physical market place and etc. In the study of Tandon [13] identified that website functionality has positive impact on customer satisfaction on online shopping in Indian context. When consider about the Sri Lankan context, this study also identified that website functionality has significant influence on customer satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, this study in line with pervious findings in the literature (Sakar, 2011;Özen&Kodaz, 2016;Fang, Wen, George, &Prybutok, 2016;Mohseni, Jayashree, Rezaei, Kasim, &Okumus, 2018) validates that both shopping value and satisfaction are effective in determining the purchase intention. Several research further indicates that shopping value lead to satisfaction of online shopping consumers and somehow direct or indirect significantly promote their purchase intention (Arshad, Mahmood, Siddiqui, & Tahir, 2014;Akhondi, &Kafashpor, 2016;Tandon, Kiran, &Sah, 2017). Findings from this study reveal that matured consumers' satisfaction acts as an important mediator partially mediated the relationship between shopping value and purchase intention (see Fig2).…”
Section: Discussionmentioning
confidence: 60%
“…According to Chung and Shin [24] the decision of customers to continue or discontinue their relationship with the product or service it is highly dependent on customer satisfaction. In an e-commerce environment, customer satisfaction impacts on retaining old customers and introducing new customers [25]. Alam and Yasin [26] recognize website design, reliability, product variety and delivery performance as an important antecedent of customer satisfaction in online shopping.…”
Section: Satisfactionmentioning
confidence: 99%